Coal mining as a risk factor for tuberculosis – Commodity or circumstance? - Nevadna Singh; Elvis M. Irusen (Southern African Journal of Infectious Diseases)
The association of tuberculosis (TB) with the mining industry is well known in South Africa. This may well be true for gold mining and silica exposure. However, a description of the pathophysiological link between coal mining and TB is not clearly detailed in the literature with many articles citing associations rather than direct causality. A focused intervention of active case-finding and treatment in coal mines in South Africa resulted in a dramatic reduction in the incidence of TB of more than 70% compared to historical figures and substantially below the national incidence as well.